DISTRIBUTED WEB SERVICE REPOSITORY - Nawrocki, Piotr; Mamla, Aleksander (Computer Science, 2015)
The increasing availability and popularity of computer systems has resulted in a demand for new, language- and platform-independent ways of data exchange. That demand has in turn led to a significant growth in the importance of systems based on Web services. Alongside the growing number of systems accessible via Web services came the need for specialized data repositories that could offer effective means of searching of available services. The development of mobile systems and wireless data transmission technologies has allowed the use of distributed devices and computer systems on a greater scale. The accelerating growth of distributed systems might be a good reason to consider the development of distributed Web service repositories with built-in mechanisms for data migration and synchronization.